Cinacalcet Rectifies Hypercalcemia in a Patient With Familial Hypocalciuric Hypercalcemia Type 2 (FHH2) Caused by a Germline Loss‐of‐Function Gα11 Mutation. (22nd September 2017) - Gorvin, Caroline M; Hannan, Fadil M; Cranston, Treena; Valta, Helena; Makitie, Outi; Schalin‐Jantti, Camilla; Thakker, Rajesh V
ABSTRACT: G‐protein subunit α‐11 (Gα11 ) couples the calcium‐sensing receptor (CaSR) to phospholipase C (PLC)‐mediated intracellular calcium (Ca 2+ i ) and mitogen‐activated protein kinase (MAPK) signaling, which in the parathyroid glands and kidneys regulates parathyroid hormone release and urinary calcium excretion, respectively. Heterozygous germline loss‐of‐function Gα11 mutations cause familial hypocalciuric hypercalcemia type 2 (FHH2), for which effective therapies are currently not available. Here, we report a novel heterozygous Gα11 germline mutation, Phe220Ser, which was associated with hypercalcemia in a family with FHH2. Homology modeling showed the wild‐type (WT) Phe220 nonpolar residue to form part of a cluster of hydrophobic residues within a highly conserved cleft region of Gα11, which binds to and activates PLC; and predicted that substitution of Phe220 with the mutant Ser220 polar hydrophilic residue would disrupt PLC‐mediated signaling. In vitro studies involving transient transfection of WT and mutant Gα11 proteins into HEK293 cells, which express the CaSR, showed the mutant Ser220 Gα11 protein to impair CaSR‐mediated Ca 2+ i and extracellular signal‐regulated kinase 1/2 (ERK) MAPK signaling, consistent with diminished activation of PLC. Furthermore, engineered mutagenesis studies demonstrated that loss of hydrophobicity within the Gα11 cleft region also impaired signaling by PLC. The loss‐of‐function associated with the Ser220 Gα11 mutant was rectified by treatment of cells with cinacalcet, which is a CaSR‐positive allosteric modulator. Furthermore, in vivo administration of cinacalcet to the proband harboring the Phe220Ser Gα11 mutation, normalized serum ionized calcium concentrations. Thus, our studies, which report a novel Gα11 germline mutation (Phe220Ser) in a family with FHH2, reveal the importance of the Gα11 hydrophobic cleft region for CaSR‐mediated activation of PLC, and show that allosteric CaSR modulation can rectify the loss‐of‐function Phe220Ser mutation and ameliorate the hypercalcemia associated with FHH2. © 2017 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.